Stroke syndromes - Bogousslavsky, Julien; Caplan, Louis R. (Cambridge : Cambridge University Press, 2001)
The first edition of Stroke Syndromes was widely welcomed as a new and authoritative reference in the assessment and diagnosis of stroke. This revised and updated edition remains the definitive guide to patterns and syndromes in stroke. A comprehensive survey of all types of neurological, neurophysiological and other clinical dysfunction due to stroke, the book is organised to make pattern recognition easier. It contains descriptions of clinical problems encountered in stroke patients and their differential diagnosis, and will enable clinicians to differentiate between possible locations on the basis of symptoms and signs. A companion volume Uncommon Causes of Stroke completes this highly authoritative reference work which clinicians in neurology will find essential to the understanding and diagnosis of stroke.
1. Stroke onset and courses / Haruko Yamamoto, Masayasu Matsumoto and Kazuo Hashikawa / [et al.] -- 2. Clinical types of transient ischemic attacks / Graeme J. Hankey -- 3. Hemiparesis and other types of motor weakness / Teresa Pinho e Melo and Julien Bogousslavsky -- 4. Sensory abnormality / Jong Sung Kim -- 5. Cerebellar ataxia / Dagmar Timmann and Hans Christoph Diener -- 6. Headache: stroke symptoms and signs / Conrado J. Estol -- 7. Eye movement abnormalities / Charles Pierrot-Deseilligny -- 8. Cerebral visual dysfunction / Jason J. S. Barton and Louis R. Caplan -- 9. Visual symptoms (eye) / Shirley H. Wray -- 10. Vestibular syndromes and vertigo / Marianne Dieterich and Thomas Brandt -- 11. Auditory disorders in stroke / Robert A. Levine and Rudolf Hausler -- 12. Abnormal movements / Joseph Ghika and Julien Bogousslavsky -- 13. Seizures and stroke / Anne L. Abbott, Christopher F. Bladin and Geoffrey A. Donnan -- 14. Disturbances of consciousness and sleep-wake functions / Claudio Bassetti -- 15. Aphasia and stroke / Andrew Kertesz -- 16. Agitation and delirium / John C. M. Brust and Louis R. Caplan -- 17. Frontal lobe stroke syndromes / Paul J. Eslinger and Raymond K. Reichwein -- 18. Memory loss / Jose M. Ferro and Isabel P. Martins -- 19. Neurobehavioural aspects of deep hemisphere stroke / Jose M. Ferro -- 20. Right hemisphere syndromes / Stephanie Clarke -- 21. Poststroke dementia / Didier Leys and Florence Pasquier -- 22. Disorders of mood behaviour / Florence Ghika-Schmid and Julien Bogousslavsky -- 23. Agnosias, apraxias and callosal disconnection syndromes / Patrik Vuilleumier -- 24. Muscle, peripheral nerve and autonomic changes / Thierry Kuntzer and Bernard Waeber -- 25. Dysarthria / Paola Santalucia and Edward Feldmann -- 26. Dysphagia and aspiration syndromes / Mark J. Alberts and Jennifer Horner-Catt -- 27. Respiratory dysfunction / Francois Vingerhoets and Julien Bogousslavsky -- 28. Clinical aspects and Correlates of stroke recovery / Marta Altieri, Vittorio Di Piero and Edoardo Vicenzini / [et al.] -- 29. Arterial territories of human brain / Laurent Tatu, Thierry Moulin and Julien Bogousslavsky / [et al.] -- 30. Superficial middle cerebral artery syndromes / Jean-Philippe Neau and Julien Bogousslavsky -- 31. Lenticulostriate arteries / Patrick Pullicino -- 32. Anterior cerebral artery / John C. M. Brust, Tohru Sawada and Seiji Kazui -- 33. Anterior choroidal artery territory infarcts / Philippe Vuadens and Julien Bogousslavsky -- 34. Thalamic infarcts and hemorrhages / Alain Barth, Julien Bogousslavsky and Louis R. Caplan -- 35. Caudate infarcts and hemorrhages / Chin-Sang Chung, Hye-Seung Lee and Louis R. Caplan -- 36. Posterior cerebral artery / Claudia J. Chaves and Louis R. Caplan -- 37. Large and panhemispheric infarcts / Stefan Schwarz, Stefan Schwab and Werner Hacke -- 38. Multiple, multilevel and bihemispheric infarcts / Emre Kumral -- 39. Midbrain infarcts / Marc Hommel and Gerard Besson -- 40. Pontine infarcts and hemorrhages / Chin-Sang Chung and Louis R. Caplan -- 41. Medullary infarcts and hemorrhages / Bo Norrving -- 42. Cerebellar stroke syndromes / Pierre Amarenco -- 43. Extended infarcts in the posterior circulation (brainstem/cerebellum) / Barbara E. Tettenborn -- 44. Border zone infarcts / E. Bernd Ringelstein and Florian Stogbauer -- 45. Classical lacunar syndromes / John M. Bamford -- 46. Putaminal hemorrhages / Kazuo Minematsu and Takenori Yamaguchi -- 47. Lobar hemorrhages / Carlos S. Kase -- 48. Intraventricular hemorrhages / Peter C. Gates -- 49. Subarachnoid hemorrhage syndromes / Jan van Gijn and Gabriel J. E. Rinkel -- 50. Brain venous thrombosis syndromes / Caroline Arquizan, Jean-Francois Meder and Jean-Louis Mas -- 51. Carotid occlusion syndromes / Francois Nicoli and Julien Bogousslavsky -- 52. Cervical artery dissection syndromes / Tobias Brandt, Erdem Orberk and Werner Hacke -- 53. Syndromes related to large artery thromboembolism within the vertebrobasilar system / Louis R. Caplan -- 54. Spinal stroke syndromes / Matthias Sturzenegger.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Cerebrovascular disease -- Diagnosis; Diagnosis, Differential; Symptoms